PENGARUH CAR, NPL DAN LDR TERHADAP PROFITABILITAS STUDI PADA BPD PULAU SULAWESI - Subiyakta, Dhea Hervina; Soelistyo, Aris (Journal of Financial Economics & Investment, 2021)
The Regional Development Bank is one of the banking institutions in Indonesia where ownership of shares is in the hands of the Regional Provincial Government. The measurement of the level of profitability can use the ratio of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Loan To Deposit Ratio (LDR).The study was conducted to determine the effect of the capital adequacy ratio, non-performing loan, and loan to deposit ratio on the profitability of Regional Development Banks (BPD) in Sulawesi Island. The data used is inferior data obtained indirectly through the official website of each Regional Development Bank. Research testing is done by using panel data regression. The results of the research test found that based on the F statistical test, a probability value of 0.000416 was obtained, indicating that the CAR, NPL and LDR variables had a significant effect on ROA simultaneously. While in the T test, the Capital Adequacy Ratio variable has a positive and significant effect on the profitability of Regional Development Banks in Sulawesi Island. Meanwhile, the other two variables, namely the Non-Performing Loan and Loan To Deposit Ratio have a positive and insignificant effect on the profitability of Regional Development Banks in Sulawesi Island.